PENERAPAN EKONOMI SIRKULER DALAM MENGURANGI EMISI KARBON DI PROVINSI SULAWESI TENGGARA - Farih, Muhamad; HM, Suyuti; Titop, Herman; Mariani; Imran (STIE Mahardhika, 2025)
This research aims to analyze the perceptions of the people of Southeast Sulawesi regarding the implementation of a circular economy in an effort to reduce carbon emissions. The circular economy offers a sustainable economic model that focuses on reducing waste through recycling, reuse, and extending the life of products. In Southeast Sulawesi, waste generation predominantly comes from households around 60% and is dominated by food waste 53.22%, providing great opportunities for implementing a circular economy. The research results show that people have a positive attitude towards the circular economy, as indicated by the average value of the questionnaire items, which ranges from 3.37 to 3.83. However, there are variations in perception that indicate the need for further outreach in several aspects of the circular economy. In conclusion, implementing a circular economy in Southeast Sulawesi can contribute significantly to reducing carbon emissions through better waste management and increasing community participation. Government policy support and public education are very important to strengthen the circular economy as a sustainable strategy in this area. This research provides a basis for developing evidence-based programs to achieve environmental sustainability in Southeast Sulawesi.